Technological Effectiveness of Sugar-Industry Effluent Methane Fermentation in a Fluidized Active Filling Reactor (FAF-R) - Marcin Dębowski; Marcin Zieliński (Energies, 2020)
Technological solutions allowing the increase of the technological efficiency of anaerobic methods of wastewater treatment are still under investigation. The weaknesses of these solutions can be limited by the use of active fillings. The aim of the present study was to determine the impact of fluidized active filling on the effectiveness of anaerobic treatment of sugar-industry effluent, the production efficiency and the qualitative composition of the biogas produced. High, comparable (p = 0.05) effluent treatment results were observed at tested organic load rates between 4.0 and 6.0 kg COD (Chemical Oxygen Demand)/m3·d. The COD removal rate reached over 74%, biogas yields ranged from 356 ± 25 to 427 ± 14 dm3/kg CODremoved and the average methane contents were approximately 70%. A significant decrease in effluent treatment efficiency and methane fermentation was observed after increasing the organic load rate to 8.0 kg COD/m3·d, which correlated with decreased pH and FOS/TAC (volatile organic acid and buffer capacity ratio) increased to 0.44 ± 0.2. The use of fluidized active filling led to phosphorus removal with an efficiency ranged from 64.4 ± 2.4 to 81.2 ± 8.2% depending on the stage. Low concentration of total suspended solids in the treated effluent was also observed.